A note on the translation of Marinus' Introduction to Euclid's Data - Sialaros, Michalis (Neusis, 2024)
Back in 1896, Heinrich Menge published the critical edition of the Introduction to Euclid’s Data, one of the two extant works by Marinus of Neapolis, accompanied by a Latin translation. In Menge’s work, as well as in all other translations that followed it, there appears an oversight regarding the translation of the phrase ‘τὸ λογικὸν πρὸς τὸ πεζόν’. The aim of the present note is to restore the meaning of the ancient Greek text and to examine the possible outcomes of the proposed translation.